Pemanfaatan Sistem Informasi Akuntansi Dengan Accurate Online Yang Efektif Dalam Peraturan Work From Home (WFH) di Katering Kino Surakarta - Budi Al Amin; Candra Agustina; Ahmad Fauzi (LPPM Universitas Bina Sarana Informatika, 2021)
Catering Kino is a catering that serves food orders at an event, generally weddings and seminars and factories. catering Kino is a caterer that puts forward service quality and an excellent taste image. In serving kino catering customers, customer satisfaction is prioritized from ordering to the quality of the food served and providing good facilities. So that to calculate so much inventory can be a burden on the mind for the business owner, which is basically the business owner doing it manually or just following his intuition about the amount of material needed. So we need an information system that provides accurate information. Based on the background of these problems, it is necessary to make changes by utilizing a digital or online accounting information system, namely by using the Accurate Online application. In designing a digital accounting information system, it is hoped that it can help the owner in managing the company's operations